Adaptación psicométrica de un instrumento de procrastinación específico al contexto laboral en trabajadores peruanos - Guzmán-Alvarado, Milagos (2025)
Procrastination is a psychological construct that has been studied in recent years in the labor context, due to a recent measurement model for labor procrastination. This model consists of a psychometric study of labor procrastination, based on 2 dimensions, Cyberslaking (laziness associated with internet use) and Soldiering (Sense of service). The objective of this study is to present initial results of structural and convergent / divergent validity of the adaptation of the Procrastination Scale at Work in a Peruvian sample of workers. For this, this scale was adapted to Spanish by the authors of this study. Subsequently, 241 workers from different occupations participated, responding to the scale online or in person. With the information collected, a semi-confirmatory analysis and convergent and divergent validity were performed with measures of general procrastination, anxiety and depression. A one-dimensional structure was found, with a reduction of items; as evidence of convergent validity, the scores correlated with the general procrastination; As evidence of divergent validity, the new version of PAWS correlated near zero with symptoms of anxiety and depression. It is concluded that labor procrastination can be estimated with a modified one-dimensional measure, but that its structure is required to be replicated.